The Influence Of The Family Hope Program In Improving The Economy Of The Poor Community Beneficiaries (Case Study Of Tanjung Selamat Village Medan Tuntungan District) - Damanik, Ricky Maharani; Hasanah, Uswatun (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
The Family Hope Program (PKH) is a social assistance program provided to help poor families in rural areas. According to the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 1 of 2018 concerning the Family Hope Program, it is explained that "to improve the quality of life of poor and vulnerable families by increasing accessibility to health services, education, and social welfare. This study was conducted on participants of the Family Hope Program (PKM) in Tanjung Selamat Village, Medan Tuntungan District, the purpose of this study was to determine whether the Family Hope Program (PKH) had an effect on Improving the Economy of Beneficiary Families (KPM) in Tanjung Selamat Village, Medan Tuntungan District. The method used in this study is a quantitative method applied to 64 samples used as respondents using the Slovin technique, a Likert scale. The results of the study concluded that the R square value of 0.416 means that the percentage of the influence of the Family Hope Program (PKH) on Improving the Economy of Poor Beneficiary Communities is 41.6% while the remaining 58.4% is influenced by other variables not included in the regression model. There is a regression equation Y = 64,233 + 0.676 x. Where the PKH variable (X) has a positive and significant effect on the welfare variable (Y). Test hypothesis obtained t count of 3.338. From the t hypothesis test, the researcher's initial hypothesis was answered, namely if t count > t table (3.338 > 1.986) then the conclusion of this study is that there is an influence of the Family Hope Program (PKH) on improving the economy of Beneficiary Families (KPM) in Tanjung Selamat Village, Medan Tuntungan District.